KORELASI FAKTOR PREDISPOSISI DENGAN PICKY EATER - Noorma, Nilam; Wahyuni, Maria Magdalena Dwi; Mahendika, Devin; Tasripin, Mellysa Wulandari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The incidence of picky eaters in children can be influenced by various interrelated factors. One of the main factors that influence is the food factor itself. The purpose of the study was to determine the correlation of predisposing factors with picky eaters. The research design used in this study was case control. The research was conducted in 5 kindergartens in Kupang City. The research was conducted in July of 2023. The study population was all mothers who have preschool-age children in 5 selected kindergartens. The sample amounted to 23 cases and 23 controls. Consecutive sampling technique was used. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between maternal knowledge about nutrition (p value: 0.00) and exclusive breastfeeding (p value: 0.03) with the incidence of picky eaters. It is recommended to mothers of toddlers about the importance of maintaining children's nutrition to avoid picky eating behavior.Keywords: Exclusive Breastfeeding, Knowledge, Picky Eater